Recurrent Pneumothorax in a Patient with Post-Tuberculosis Sequelae: A Case Report - Brama, Bagus; Putra, Wayan (Malang Respiratory Journal, 2024)
Introduction: Tuberculosis and its complications could lead to a condition with a high mortality and morbidity in which those complications include hemoptysis, pleural effusions, post tubercular lung disease and spontaneous pneumothorax. Pneumothorax in one possible complication in pulmonary tuberculosis with an incidence rate up to 1.5%. Case: A 46 years old man came to emergency room due to shortness of breath that had been felt since one week before and worsened after lifting some weight things 30 minutes prior the admission, the shortness of breath was described as heavy sensation whenever patient breaths, this complaint was accompanied by pain in the right lung, he has a history of lung tuberculosis and had completed his treatment, radiology examination showed right pneumothorax and later patient was hospitalized for a week with Water Seal Drainage (WSD) placed in his right lung. One month later, patient came back to emergency room with the same symptoms and was hospitalized again, but this time, pleurodesis was done. Discussion: Tuberculosis causes damage to lung structure, and disturb its function leaving a sequelae and causing disability called post-tuberculosis lung disease (PTLD). Secondary spontaneous pneumothorax is pneumothorax that occurring in a setting of underlying lung disease. Patients with SSP tolerate pneumothorax less well and display heavier symptoms, even if the pneumothorax is relatively small in size. Conclusions: The inflammation and fibrosis process on Tuberculosis infection leaves a sequelae damage and increased the vulnerability of someone lung’s that could lead to many complications such as pneumothorax. Key words: Pneumothorax, Post-Tuberculosis Sequelae, Recurrent.